2020
DOI: 10.1136/rapm-2020-101476
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial baseline values of 15 000 patients suffering from chronic pain: Dutch DataPain study

Abstract: Background and objectivesChronic pain affects many adults. To improve our daily practice, we need to understand multidisciplinary approaches, integrated treatment plans and the biopsychosocial context of these patients. To date, almost 15 000 chronic pain patients have been referred to the Maastricht University Pain Center in the Netherlands.MethodsThis study describes 11 214 of these patients suffering from chronic pain. Chronic pain was analyzed using relevant Initiative on Methods, Measurement, and Pain Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…For more than 20 years, the Department of Anaesthesiology and Pain Medicine of the Maastricht University Medical Center+in the Netherlands has routinely collected both the NRS and PGIC of chronic pain patients for both interventional studies and a cohort data. For this study, we used data of the RCT’s of van Eerd, et al, 11 Kallewaard et al, 12 Slangen, et al, 13 and Kemler et al 14 and cohort data of the DATA PAIN cohort, initiated in 2003 by the Comprehensive Multidisciplinary University Pain Center Maastricht 2 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For more than 20 years, the Department of Anaesthesiology and Pain Medicine of the Maastricht University Medical Center+in the Netherlands has routinely collected both the NRS and PGIC of chronic pain patients for both interventional studies and a cohort data. For this study, we used data of the RCT’s of van Eerd, et al, 11 Kallewaard et al, 12 Slangen, et al, 13 and Kemler et al 14 and cohort data of the DATA PAIN cohort, initiated in 2003 by the Comprehensive Multidisciplinary University Pain Center Maastricht 2 …”
Section: Methodsmentioning
confidence: 99%
“…For this study, we used data of the RCT’s of van Eerd, et al, 11 Kallewaard et al, 12 Slangen, et al, 13 and Kemler et al 14 and cohort data of the DATA PAIN cohort, initiated in 2003 by the Comprehensive Multidisciplinary University Pain Center Maastricht. 2 To perform this secondary analysis, approval was obtained by the medical ethical committee of the Maastricht University (METC approval number: 2020‐2391). All studies included followed the recommendations of the IMMPACT guidelines on core outcomes for an adequate evaluation of the treatment efficacy and effectiveness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study reported that the incidence of chronic pelvic pain catastrophizing was 53.1% (Sewell et al, 2018). Moreover, in a study of 11,214 patients with chronic pain, 39% patients reported severe pain catastrophizing (Brouwer et al, 2020). Evidence has suggested that pain catastrophizing has a consistently strong correlation with pain severity, disability, performance-based physical functioning and mood among people with chronic pain (Flor et al, 1993;Geisser et al, 1994;Thomtén et al, 2016;Salt et al, 2018;Varallo et al, 2021b).…”
Section: Introductionmentioning
confidence: 98%